2016
DOI: 10.3390/md14110213
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Individual Disulfide Bonds of μ-Conotoxin GIIIA in the Inhibition of NaV1.4

Abstract: μ-Conotoxin GIIIA, a peptide toxin isolated from Conus geographus, preferentially blocks the skeletal muscle sodium channel NaV1.4. GIIIA folds compactly to a pyramidal structure stabilized by three disulfide bonds. To assess the contributions of individual disulfide bonds of GIIIA to the blockade of NaV1.4, seven disulfide-deficient analogues were prepared and characterized, each with one, two, or three pairs of disulfide-bonded Cys residues replaced with Ala. The inhibitory potency of the analogues against N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Fifteen different disulfide isomers are possible for a peptide containing six cysteines, and still three different isomers (ribbon, bead, and globular) might occur in case of four cysteines. It has, however, not been mentioned in the report by Han et al 46 which isomer of the μ-GIIIA analogs has been tested because the structural characterization of the respective products was not performed. Apart from the reports on μ-GIIIA regarding the disulfide-deficient variants, another study by Khoo et al 47 provides an insight into the removal of disulfide bridge C1–C9 in μ-KIIIA, resulting in only a minimal change in the biological activity against Na V 1.2 and Na V 1.4.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen different disulfide isomers are possible for a peptide containing six cysteines, and still three different isomers (ribbon, bead, and globular) might occur in case of four cysteines. It has, however, not been mentioned in the report by Han et al 46 which isomer of the μ-GIIIA analogs has been tested because the structural characterization of the respective products was not performed. Apart from the reports on μ-GIIIA regarding the disulfide-deficient variants, another study by Khoo et al 47 provides an insight into the removal of disulfide bridge C1–C9 in μ-KIIIA, resulting in only a minimal change in the biological activity against Na V 1.2 and Na V 1.4.…”
Section: Discussionmentioning
confidence: 99%
“…Several disulfide bond replacement strategies have been investigated for generating conotoxin with improved potential as drug leads, including the substitution of disulfide bonds with other cross-links such as diseleno, triazole, dithiol, dicarba, lactam, and thioether bridges and their deletion by replacement of Cys with residues unable to cross-link (which we thereafter call “deletion”). …”
Section: Introductionmentioning
confidence: 99%
“…For example, in the scorpion toxin leiurotoxin I, the μ-conotoxin KIIIA, the leech carboxypeptidase inhibitor, and the α-conotoxin Vc1.1, one disulfide bond was removed without a significant loss of inhibitory potential. In contrast, Han et al showed that in the case of μ-GIIIA, all three disulfide bridges were essential for bioactivity …”
Section: Introductionmentioning
confidence: 89%
“…In contrast, Han et al showed that in the case of μ-GIIIA, all three disulfide bridges were essential for bioactivity. 20 The aim of the present study was thus to explore the influence of the common disulfide bridge C 19 −C 25 on the structure and function of FXIIIa inhibitor tridegin. In a combined approach of experimental and computational studies, the three 2-disulfide-bonded tridegin isomers (bead, ribbon, and globular fold) 21 were synthesized and evaluated for their FXIIIa inhibitory activity and their structural stability based on earlier established models of the 3-disulfide-bonded tridegin.…”
Section: ■ Introductionmentioning
confidence: 99%